2017
DOI: 10.1002/brb3.741
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal atrophy, asymmetry, and cognition in type 2 diabetes mellitus

Abstract: IntroductionType 2 diabetes mellitus is associated with global and hippocampal atrophy and cognitive deficits, and some studies suggest that the right hippocampus may display greater vulnerability than the left.MethodsHippocampal volumes, the hippocampal asymmetry index, and cognitive functioning were assessed in 120 nondemented adults with long duration type 2 diabetes.ResultsThe majority of the sample displayed left greater than right hippocampal asymmetry (which is the reverse of the expected direction seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 41 publications
0
28
0
1
Order By: Relevance
“…However, Topiwala et al (2017) found different right-left hippocampal vulnerability to alcohol exposure, again suggesting differential vulnerability between the right and left hippocampus to certain exposures. Similarly, prior studies in groups with other types of injury or disease such as traumatic brain injury, diabetes, and dementia also have found asymmetrical effects on hippocampal volumes (Bigler et al, 1996;Milne et al, 2018;Shi et al, 2009). In addition to potential asymmetrical hippocampal volume loss associate with injury, prior work has also suggested hippocampal asymmetry in healthy subjects, typically with the right hippocampus having greater volume than the left (Pedraza et al, 2004;Woolard and Heckers, 2012).…”
Section: Discussionmentioning
confidence: 87%
“…However, Topiwala et al (2017) found different right-left hippocampal vulnerability to alcohol exposure, again suggesting differential vulnerability between the right and left hippocampus to certain exposures. Similarly, prior studies in groups with other types of injury or disease such as traumatic brain injury, diabetes, and dementia also have found asymmetrical effects on hippocampal volumes (Bigler et al, 1996;Milne et al, 2018;Shi et al, 2009). In addition to potential asymmetrical hippocampal volume loss associate with injury, prior work has also suggested hippocampal asymmetry in healthy subjects, typically with the right hippocampus having greater volume than the left (Pedraza et al, 2004;Woolard and Heckers, 2012).…”
Section: Discussionmentioning
confidence: 87%
“…Recently, addressing hippocampal asymmetry and its relationship with cognitive decline in people with Type 2 diabetes in particular, Milne et al . have found that asymmetric hippocampal atrophy, more pronounced in the right hippocampus, contributes to cognitive decrements in in people with Type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes-induced brain injury manifests as neurodegeneration, cerebral infarction, and progressive cognitive decline. [5][6][7] Evidence arising from diabetic animal models indicates that neuronal death is one of the major factors causing brain injury. 8,9 However, the underlying molecular mechanism of neuronal death in DM is still unclear.…”
Section: Introductionmentioning
confidence: 99%